Komunikasi Green Influencer Lokal dalam Membangun Kesadaran Konservasi Laut Berbasis Ecotourism di Kalimantan Timur - Dwivayani, Kadek Dristiana; Rizky, Salsabilla (Nusantara Innovation Journal, 2025)
This study aims to examine the role of local green influencers in interacting and building public awareness of ecosystem conservation through ecotourism activities in East Kalimantan. The background of the study is based on the increasing threat of environmental degradation due to economic activities, so that an innovative approach based on community participation is needed to support environmental preservation and the development of sustainable tourism. Local green influencers, who actively use digital media to disseminate environmental conservation messages, are considered to have significant potential in raising public awareness and promoting environmentally friendly ecotourism practices. This research approach uses a descriptive qualitative method with in-depth interviews. Social media content analysis of green influencer accounts was also conducted to understand the message strategies and interaction patterns developed to promote conservation awareness. The results show that local green influencer communication is effective in building environmental awareness through educational narratives and active engagement with local communities. Influencers successfully create positive social change by encouraging public participation in sustainable conservation practices based on ecotourism. The credibility of the source influences how environmental messages are received and believed by the public. Factors such as the expertise, trustworthiness, and attractiveness of the communicator play a significant role in shaping public perception of environmental issues. The research results revealed that the role of local green influencer communication is an important force in creating collective awareness and supporting the development of ecotourism that is oriented towards ecosystem conservation.